Comparative analysis among eletrical resistivity tomography arrays in the reconnaissance of flow structure in fractures aquifer in caçapava do sul (RS) - Moreira, César Augusto [UNESP]; Helene, Lívia Portes Innocenti [UNESP]; Rosa, Fernanda Teles Gomes [UNESP]; Hansen, Marco Antônio Fontoura; Malagutti Filho, Walter [UNESP]; Dourado, João Carlos [UNESP] (Universidade Federal do Rio Grande do Sul, 2019)
This paper performs presents a comparative analysis between data from detailed electrical resistivity tomography data acquired through the dipole-dipole, Schlumberger and Wenner arrays of detail, obtained on a ground where granite terrain in Caçapava do Sul (RS) where groundwater flows in occurs underground flow in a fractured aquifer system, acquired through the arrangements make dipole-dipole, Schlumberger and Wenner. Structural data obtained on rocks exposed in 100 m and 300 m offrom the study area served as a fundamental the basis for analysisthe analysis of geophysical products and the definition of the mathematical model that is more feasible with the reality. The predominant fracture direction in the region has E/W orientation with two main senses of diving. By the results of the three arrays, it was possible to recognize areas of low resistivity related to water accumulation, with values lower than 70 Ω.m, in contrast to values higher than 1000 Ω.m typical of unaltered rock. The results of the arrangement allowed Schlumberger array allowed a 3D modeling a surface of low resistivity surface with orientation and dive compatible with the fracture system recognized in field, ih this way this array showed a more realist model guidance and diving are compatible with systems of fractures found in rock, to the of the geological structures in detriment to the other results, which do not allow subsidies for an adequate definition of sites for drilling wells.
Análise comparativa entre arranjos de tomografia elétrica no reconhecimento de estruturas de fluxo em aquífero fraturado em caçapava do sul (rs)
Keywords: Dipole-dipole; Electrical resistivity tomography; Fractured aquifer; Geophysics; Schlumberger; Wenner